2006
DOI: 10.1111/j.1547-5069.2006.00082.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Computer Technology to Enhance Immigrant Families' Adaptation

Abstract: Study findings warrant further exploration to assess bow new computer technology promotes immigrant families' adaptation and alleviates stress associated with resettlement, including information about their health and health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 28 publications
(37 reference statements)
0
16
1
1
Order By: Relevance
“…Like almost everyone else today, undocumented immigrants are users of information and communication technology (ICT). While ICTs have been found to support immigrants' integration in new contexts [27,28,31,94], technology can also enable discrimination, harassment, and government surveillance, the latter potentially leading to devastating consequences such as detention, deportation, and family disruption. For the estimated 11.3 million undocumented immigrants in the United States [71], these risks have intensified recently due to increased immigration enforcement and anti-immigrant sentiment [52,53,57].…”
Section: Introductionmentioning
confidence: 99%
“…Like almost everyone else today, undocumented immigrants are users of information and communication technology (ICT). While ICTs have been found to support immigrants' integration in new contexts [27,28,31,94], technology can also enable discrimination, harassment, and government surveillance, the latter potentially leading to devastating consequences such as detention, deportation, and family disruption. For the estimated 11.3 million undocumented immigrants in the United States [71], these risks have intensified recently due to increased immigration enforcement and anti-immigrant sentiment [52,53,57].…”
Section: Introductionmentioning
confidence: 99%
“…A challenge faced by many immigrants as well as the host country is integration of the immigrant population into the new community (Scott & Scott, 2013;Su'arez-Orozco, Suárez-Orozco, & Qin-Hilliard, 2014). There have been attempts in studying the role of technology in tackling this challenge (Tsai, 2006). For example, immigrants have a substantial information need in adapting to the new society and it has been shown that technology can benefit immigrants by supporting their information and practical needs in adjusting to living in a new country (Shoham & Strauss, 2008;Fisher, Durrance, & Hinton, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…There has not been any work investigating at what level hyper-local online communities can help immigrants integrate in the host community. Computer technology can assist immigrant families in overcoming barriers posed by loss of social networks, social disconnection, and limited language proficiency (Tsai, 2006). There is some concern that immigrants' use of internet technologies can increase their isolation in their new community.…”
Section: Introductionmentioning
confidence: 99%
“…2007). Immigrants generally face problems because of obstacles in language and interpersonal relationships (Bhugra 2004, Tsai 2006, Lee 2007). In a new country, immigrants face the loss of old social networks support (Wong et al.…”
Section: Introductionmentioning
confidence: 99%